Effect of aquilaria malaccensis after undergoes vacuum far-infrared radiation drying: article / Mohammmad Nur Hazrul A Hamid, Habsah Alwi - A Hamid, Mohammmad Nur Hazrul; Alwi, Habsah (2017)
Vacuum Far-infrared Radiation (VFIR) is a technique of drying that has been used actively widely in food processing industry to replace conventional drying as it proven its effectiveness and many other benefits. The VFIR of Aquilaria Malaccensis leaves took place in order to determine the value of this agarwood parts compared to the normal studies of its bark. The purpose of this experiment is to determine the concentration of antipyretic inside the leaves. Antipyretic reagent can be found mainly in acetaminophen product such as paracetamol. Samples are dried under vacuum constant vacuum condition 200 mbar divided to three temperatures, 40 C, 50 C and 60 C for 4 hours. The moisture content of each sample was taken to discover the moisture loss from the samples. Then, the leaves undergone extraction procedure using soxhlet method and analysed by High Performance-Liquid Chromatography (HPLC) under wavelength 200 nm to determine concentration of antipyretic in the leaves using mobile phase Acetonitrile-deionized water (30:70). From the findings, the concentration of antipyretic varies at different temperature of drying. The most optimum to preserve the active compound using VFIR set to be 60 C based on findings.